Kesawan Square in Heritage Tourism: Historical Dynamics and Digital Transformation, 2010-2025 - Flores Tanjung; Pulung Sumantri (Mahesa Research Center (PT. Mahesa Global Publishing), 2025)
This study investigates the evolving dynamics of the Kesawan Area in Medan City as a heritage tourism destination from 2010 to 2025. Its primary aim is to analyze the processes of revitalization, branding strategies, and digital transformation undertaken to establish Kesawan as a historical icon of the city, while also examining how these processes shape perceptions of heritage. The research employs a qualitative approach with a descriptive-historical method, drawing on field observations, interviews, and documentation. The findings indicate that the period 2010–2020 marked the initial phase of revitalization, characterized by heritage branding through cultural festivals, architectural preservation, and the promotion of regional identity. In contrast, the period 2020–2025 witnessed the adoption of smart tourism and digital technologies, which significantly increased tourist visits and stimulated the growth of local micro, small, and medium enterprises. Strong branding reinforced Kesawan’s historical image, while digital transformation expanded accessibility and enhanced tourist engagement, despite persistent challenges such as the digital divide and the risk of commodification. The study underscores that heritage preservation can be managed adaptively and sustainably through the integration of branding strategies and digital innovation. Theoretically, it contributes to the field of heritage tourism by offering insights into how historical dynamics and digital transformation intersect to shape the meaning of heritage within urban spaces.